Allergic Contact Dermatitis Reaction to Permanent Tattoo Containing Paraphenylenediamine: A Case Report - Eliot Parascandolo; Samuel Puglisi; Miguel Marenco; Gregory Puglisi (Case Reports in Immunology)
Paraphenylenediamine (PPD) is a well-known culprit allergen in the literature and clinical practice. Although this has been described in temporary tattoos, the definite implication of PPD in permanent tattoos has not been described. We report a patient who developed severe allergic contact dermatitis (ACD) requiring skin grafting after receiving a permanent tattoo with ink containing PPD. A 30-year-old female with a past history of atopic dermatitis and psoriasis presented with a 2-week history of cutaneous reaction to a recent tattoo. The patient noticed inflammation and irritation of the tattoo site the day after administration. The patient was previously identified on patch testing to have a PPD allergy after evaluation for dermatitis after hair dye application. Following the tattoo placement, she applied soap and bacitracin cream which she had used several years prior on a similar tattoo. On presentation 2 weeks later, she was found to have a deep ulcerated plaque with an indurated border encompassing the area of the tattoo. She was referred to the emergency department and admitted for treatment, ultimately requiring debridement and skin grafting. The patient obtained the safety data sheets for the tattoo inks which revealed PPD as an ingredient in every color. We believe this is the first confirmed case of PPD being implicated as the causative agent for ACD to a permanent tattoo. Tattoo ink is unregulated, and formulas are proprietary which makes safe practice difficult for patients with sensitivities. We advocate for consistent ingredient labeling, regulation, and transparency within the tattoo ink industry.